Enhanced catalytic performance of 3 %FeCu-HC modified hydrochar for methyl violet 2B removal in the heterogeneous fenton process: Synthesis and optimization - Abderrazzak Adachi; Omar Boualam; Tarik El Houari Salmani; Fatima Moussaoui; Amal Lahkimi (Next Materials, 2025)
Recently, the use of biomass waste has attracted considerable interest, particularly for water purification. In this study, a modified hydrochar from almond shells (AS) codoped with a Fe-Cu bimetal (3 %FeCu-HC) was prepared by hydrothermal carbonization and wet impregnation, followed by pyrolysis. The bimetallic catalyst has been designed to promote the activation of hydrogen peroxide (H2O2) to remove the organic pollutant (MV2B). The prepared 3 %FeCu-HC could degrade 93.51 % of MV2B by activating H2O2 at pH 7.5. The composition and structure of bimetallic catalysts (3 %FeCu-HC) were characterized, using X-ray diffraction (XRD), scanning electron microscopy coupled to EDS analysis (SEM-EDS), Fourier transform infrared spectroscopy (FTIR), and specific surface area analysis using the Brunauer, Emmett, and Teller (BET) method. Hydroxyl radicals (OH.) were identified as the main reactive species in the heterogeneous Fenton process, as they played a key role in the Fe3+/Fe3+, Cu2+/Cu+, and Fe3+/Cu+ redox cycles. Consequently, the 3 %FeCu-HC prepared in this way, with the advantages of high removal efficiency, good reusability, and low synthesis cost, represents a potentially promising solution for the removal of persistent organic contaminants. Phytotoxicity tests based on radish seed germination demonstrated that treatment with the bimetallic 3 %FeCu-HC catalyst eliminated toxicity, achieving a 100 % germination rate after seven days, underlining the catalyst's dual effectiveness in degrading pollutants and detoxifying water.